2005
DOI: 10.1103/physrevlett.95.165501
|View full text |Cite
|
Sign up to set email alerts
|

Why Twins Do Not Grow at the Speed of Sound All the Time

Abstract: Deformation twinning occurs in various materials including metals, intermetallics, ceramics, superconductors, and even geological systems. The rate of twin growth depends on the material system, but there are no crystallographic models to understand the mechanisms of slow twin growth. The physics of twin growth is presented for bcc-Ti alloys where it is shown that octahedral interstitial sites are not conserved at the twin-matrix interface where oxygen resides. The predicted activation energy for twin growth c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…It should be emphasized that increased number of NEB images does not change the energy gradient or USFE, indicating the absence of any energetically important intermediate O positions. This new phenomenon is similar to model presented by Oberson et al [49,50] who showed that lattice reorientation during a-and b-Ti twining eliminates octahedral sites leading to O diffusion. An additional nonequilibrium interstitial site in prism SF was also illustrated by M. Ghazisaeidi et al [18].…”
Section: Restoring Forces and Stacking Faultssupporting
confidence: 69%
“…It should be emphasized that increased number of NEB images does not change the energy gradient or USFE, indicating the absence of any energetically important intermediate O positions. This new phenomenon is similar to model presented by Oberson et al [49,50] who showed that lattice reorientation during a-and b-Ti twining eliminates octahedral sites leading to O diffusion. An additional nonequilibrium interstitial site in prism SF was also illustrated by M. Ghazisaeidi et al [18].…”
Section: Restoring Forces and Stacking Faultssupporting
confidence: 69%
“…Recent mechanistic models of DSA due to Curtin et al (2006) and Soare and Curtin (2008) clearly suggest that the answer is yes. The impact of twinning (Oberson and Ankem 2005, 2008and Proust et al, 2008 and Mn additions on the PLC constitutive model also require further exploration.…”
Section: Summary Remarksmentioning
confidence: 98%
“…The presence of a shuffle in {332}h113i twinning leaves this mixed mode particularly susceptible to interference by interstitial elements such as O, resulting in time-dependent twinning. 57 Furthermore, sufficiently high concentrations of O, such as 1.2 at.% addition found in some recently developed ''gum metal'' alloys with a Ti-23Nb-0.7Ta-2Zr-1.2O (at.%) composition, could interfere with {332}h113i twinning such that {112}h111i twinning becomes the dominant stress-induced deformation mechanism even for metastable b-phase Ti alloys. 58 Additionally, sufficiently high O concentrations can also suppress the formation of stress-induced a¢¢-martensite.…”
Section: Stress-induced Hcp X-phase and Twinningmentioning
confidence: 99%